Knowledge And Relational Competences In Virtual Organisations - Słupska, Urszula (Journal of Positive Management, 2023)
Purpose: The purpose is to identify the impact of knowledge and building relational competences on the process of creating virtual organizations (VOs). Methodology: The study included companies operating in Poland. The data was collected through personal interviews. A personal interview questionnaire was used as a research tool. The questions about the value of knowledge in VOs were constructed in a way that reflected the nature of VOs. The study was conducted in 2018. Findings: The study’s findings indicate that one of the main drivers of collaboration inside a VO is the desire to learn new things through learning with partners. The growth of human resources, the exchange of experience, and the learning of new knowledge are the three most significant advantages of collaboration in a VO, in addition to the financial gains. In the process of developing a VO, relational competences are built with the use of appropriate knowledge resources, which also have an impact on the effectiveness of collaboration. Reflection on shared learning occurs in a company’s future relationships with the environment. The competitive position is improved through expanded knowledge resources and improved relational competencies. The greatest enabling and restricting factors for the creation of VOs are knowledge and experience, respectively. Originality/value: The study’s empirical findings support the idea that having access to the right knowledge resources is essential for developing relational competences throughout the virtual organization of economic activity. Keywords: virtual organisation, knowledge, cooperation, relational competences Paper type: Research paper